Comparison of Micro-Leakage from Resin-Modified Glass Ionomer Restorations in Cavities Prepared by Er:YAG (Erbium-Doped Yttrium Aluminum Garnet) Laser and Conventional Method in Primary Teeth - Bahrololoomi, Zahra (J Lasers Med Sci, 2014)
Introduction: In recent years, significant developments have been taking place in caries removal and cavity preparation using laser in dentistry. As laser use is considered for cavity preparation, it is necessary to determine the quality of restoration margins. Glass ionomer cements have great applications for conservative restoration in the pediatric field. The purpose of this in vitro study was to compare resin-modified glass ionomer restorations micro-leakage in cavities prepared by Er:YAG (Erbium-Doped Yttrium Aluminum Garnet) laser irradiation and conventional method in primary teeth. Methods: This was an in vitro experimental study. Forty primary canine teeth were divided into 2 groups: group 1 represented cavities prepared by the no. 008 diamond bur, group 2 represented cavities prepared by Er:YAG laser. After cavity preparation, samples were restored by resin-modified glass ionomer. The teeth were thermocycled for 700 cycles, placed in 2% methylene blue for 24h and sectioned in the buccolingual direction. The degree of dye penetration was scored by 3 examiners. Data was analyzed using Mann-Whitney Test. Results: There was no statistical difference in micro-leakage between the two modes of cavity preparation (P=0.862) Conclusion: Since preparing conservative cavities is very important in pediatric dentistry, it is possible to use Er:YAG laser because of its novel and portable technology. However, further investigations of other restorative materials and other laser powers are required.